Dengue and severe dengue with neurological complications: a challenge for prevention and control - Francelino, Emanuelle de Oliveira; Puccioni-Sohler, Marzia (Arquivos de Neuro-Psiquiatria, 2024)
Dengue is the main urban arbovirus in the Americas. The disease manifests in a varied spectrum: from asymptomatic cases to those with neurological involvement, which is considered a severe form of the disease. Its annual reemergence represents a serious public health problem. The rise in the number of cases causes an increase in the number of patients with neurological manifestations of the disease, which can range from headaches to more serious conditions such as encephalitis and Guillain-Barré syndrome, with high potential of death or sequelae. Dengue prevention and control strategies should also be a concern for neurologists. The aim of the present study is to carry out a narrative review of the current methods to prevent dengue fever and its severe forms, such as cases with neurological complications. The main control measures include vaccination, which is still carried out on a small scale, vector control, and individual protection. The CYD-TDV/Dengvaxia and TAK-003/DENVax vaccines, licensed for use by the Brazilian National Health Regulatory Agency (Agência Nacional de Vigilância Sanitária, ANVISA, in Portuguese), show efficacy against hospitalizations of 72.7% (95% confidence interval [95%CI]: 62.3–80.3%) and of 90.4% (95%CI: 82.6–94.7%) respectively. The TV003/TV005 vaccine, which is being studied by Intituto Butantan in Brazil, shows promising results, with an efficacy of 79.6% for symptomatic dengue. Vector control is based on biotechnological and behavioral measures, as well as on the improvement of basic sanitation conditions. The main individual protection measure is the use of topical repellents (icaridin). All of these actions represent important tools for the prevention of dengue fever and its neurological complications.
Keywords: Dengue; Disease Prevention; Vaccines; Vector Control of Diseases; Insect Repellents